Compassion satisfaction, compassion fatigue and burnout among nurses working in clinical departments at a tertiary care hospital in Karachi. - Ahmed, Tanseer; Ali, Amjad; Rasheed, Abdur; Naz, Subia (Pakistan Journal of Physiology, 2019)
Background: Nursing is an essential component of the health care system that provides care with compassion to people of all age groups who are physically or mentally ill. The objective of this study was to investigate the occurrence of compassion satisfaction, fatigue, and burnout among nurses working in the different clinical departments of a tertiary care hospital. Methodology: This cross-sectional study was conducted using convenience sampling approach among 190 nurses working at emergency, intensive care units, cardiology, and paediatric units of Liaquat National Hospital, Karachi. Approval was taken from Ethical Review Committee of Liaquat National Hospital. Data were collected between, August to September 2018 by using Professional Quality of Life (ProQoL) scale version 5. Analysis of variance (ANOVA) was used in order to identify the significant difference of compassion satisfaction, fatigue, and burnout among different clinical departments. Results: In this study, 61.0% of participants belonged to the age group of 21 to 30 years and 54.2% were female. The proportions of the average level of compassion satisfaction (CS), compassion fatigue (CF) and burnout were found 70%, 84.7%, and 94.2% respectively. Overall mean scores of CS, CF, and burnout were 36.59, 29.11, and 32.07 respectively. ANOVA confirmed that mean scores of compassion fatigue and burnout differed significantly among four clinical departments (p=0.005 and 0.014 respectively). Conclusion: Overall study participants showed average levels of compassion satisfaction, fatigue, and burnout. Significant mean differences of compassion fatigue and burnout among all selected departments were obtained. Pak J Physiol 2019;15(3):19?22